2018
DOI: 10.1016/j.memsci.2018.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Morin-based nanofiltration membranes for organic solvent separation processes

Abstract: In this work we demonstrate the successful optimization of the interfacial polymerization reaction for the manufacture of organic solvent nanofiltration membranes by replacing the toxic amines commonly used for this method with the natural occurring bio-polyphenol morin. For the manufacture of this type of OSN membrane a crosslinked PAN support was coated by interfacial polymerization using morin as the monomer of the aqueous phase and terephtaloyl chloride as the monomer of the organic phase. These membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The large number of crosslinkable hydroxyl groups as well as the strong interfacial activity of polyphenols make catechin a potential substituent to commonly used harmful phenols [23]. In our previous work [25] we used Morin, a very similar polyphenol, as one of the reactants. In this work we replaced not only the Morin, but also the hydrazine cross-linked polyacrylonitrile support with an environmentally friendly biopolymer support.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of crosslinkable hydroxyl groups as well as the strong interfacial activity of polyphenols make catechin a potential substituent to commonly used harmful phenols [23]. In our previous work [25] we used Morin, a very similar polyphenol, as one of the reactants. In this work we replaced not only the Morin, but also the hydrazine cross-linked polyacrylonitrile support with an environmentally friendly biopolymer support.…”
Section: Introductionmentioning
confidence: 99%
“…6(e). This result revealed that the CO was involved in the adsorption process 64 . Moreover, it can be observed from Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Among them, tannic acid [76][77][78][79][80], quercetin [81], morin hydrate [82], cyclodextrin [83][84][85], chitosan [86], and vanillin [87] played a well role as a reactive material, resulting in the formation of the stable selective layer having great performance. However, most of approaches have changed only one monomer.…”
Section: Selective Layer Prepared By Sustainable Sourcesmentioning
confidence: 99%